Expression analysis of a MATE-type transporter gene of Arabidopsis and its orthologues in rice and chickpea under salt stress - Nimmy, M.S.; Kumar, V.; Singh, A.K.; Jain, P.K.; Srinivasan, R. (The Indian Journal of Genetics and Plant Breeding, 2016)
Salinity is one of the major abiotic stresses that adversely affect the crop growth and productivity. Salt responsive genes belonging to MATE efflux proteins reportedly play a significant role imparting salt tolerance to plants. In the present study, AT5G52050, a putative salt responsive gene from Arabidopsis thaliana encoding MATE efflux family protein which functions as an antiporter and its orthologues in rice (LOC_Os02g45380) and chickpea (LOC101489496) have been identified. The expression pattern of these genes was validated by quantitative reverse transcription polymerase chain reaction. In silico analysis of the upstream promoter regions of these genes revealed the presence of several conserved sequence motifs related to salt response either in single or in multiple copies. A phylogenetic analysis to understand the evolutionary relationship of MATE family genes in Arabidopsis, rice and chickpea revealed conservation of MATE family genes between dicots and monocots. The genes identified in this study may serve as promising candidates for further elucidation of the salt tolerance mechanism in plants